Environmental and Pet-Associated Risk Factor for Hookworm Infection in Coastal East Kalimantan - Blego Sedionoto; Witthaya Anamnart; Muhammad Aidil Fitrah (Gema Lingkungan Kesehatan, 2026)
Hookworm infection remains an important community health concern, particularly in the coastal areas of East Kalimantan, Indonesia, where environmental conditions facilitate transmission. Key risk factors in this region include the presence of domestic animals (cats and dogs), infection in these pets, and specific types of soil surrounding households. This study aimed to determine the prevalence of hookworm infection and its association with various environmental and behavioral risk factors. A cross-sectional survey was conducted in 2019 among 213 individuals from rural areas of Kutai Kartanegara Regency. Stool specimens were examined using Kato-Katz and Koga Agar Plate (KAP) culture technique. The prevalence of hookworm infection was 33.8% (72/213). Higher infection rates were significantly associated with older age (≥13 years), agricultural occupation, poor sanitation facilities, use of unsanitary water sources, and open defecation practices. Environmental factors, including wet soil, high soil organic carbon content, low elevation, high humidity, frequent rainfall, and proximity to rivers or plantation areas, were also significantly associated with hookworm infection (p < 0.05; ORs ranged approximately from 1.7 to 2.9). The presence of hookworm-infected domestic dogs was significantly associated with human infection (p < 0.001). These findings highlight that hookworm transmission in coastal East Kalimantan is influenced by an alliance of environmental, behavioral, and animal-related factors. Comprehensive control strategies focusing on sanitation improvement, environmental management, and control of zoonotic reservoirs are essential to reduce infection rates in endemic rural setting.